Permselectivity of the glomerular capillary wall. Studies of experimental glomerulonephritis in the rat using dextran sulfate. - Bennett, C M (1976)
To determine whether the increased filtration of serum proteins after glomerular injury is the consequence of altered electrostatic properties of the glomerular capillary wall, we measured fractional clearances of the anionic polymer, dextran sulfate, in nine Munich-Wistar rats in the early autologous phase of nephrotoxic serum nephritis (NSN). In agreement with previous studied from this laboratory, whole kidney and single nephron glomerular filtration rates were normal in NSN rats despite histological evidence of glomerular injury, and despite a marked reduction in the glomerular capillary ultrafiltration coefficient to approximately one-third of normal. In the companion study (9), it was shown that in NSN rats the mean fractional clearances of neutral dextrans over the range of effective molecular radii from 18 to 42 A were reduced, compared to normla. In contrast, in the present study the mean fractional clearances for dextran sulfate over the same range of molecular radii were significantly greater than those found previously for normal Munich-Wistar rats. The fractional clearance of dextran sulfate molecules of the same molecular radius as serum albumin (approximately 36 A) was increased markedly, from 0.015 +/- 0.005 (SEM) in nonnephritic controls to 0.24 +/- 0.03 in NSN (P less than 0.001). The sialoprotein content of glomeruli, estimated by the colloidal iron reaction, was reduced in NSN rats as compared to normal controls. It is concluded that the abnormal filtration of anionic serum proteins, such as albumin, seen in glomerulopathies is, at least in part, the consequence of loss of fixed negative charges from the glomerular capillary wall.